PESAN DAKWAH DALAM TRADISI MACOPAT DI DUSUN MORALAS DESA KARDULUK KECAMATAN PRAGAAN - Uswatun Hasanah (Reflektika, 2020)
Da'wah is one of the processes of the entry of Islam into Indonesia through culture, so the entry of Islam into Indonesia is quite short because the surrounding community is already attached to the local culture, so that the entry of Islam is subtle without going through violence, because Islam itself respects the pluralism of a society. Human relations with da'wah also study about humans and all the culture they have, humans are social beings while da'wah is the object. One example of da'wah combined with culture by Wali Songo is the Durma song "Tiger" which was created by Sunan Bonang. The researcher chose to examine the content of da'wah in the macopat tradition because it is still not revealed about the content of da'wah in a culture, including the macopat tradition. This study aims to determine the types of macopat in the hamlet of Moralas and the message of da'wah contained in the macopat tradition. This research method uses qualitative research and the type of research used is ethnographic type. Ethnography is a series of research activities to understand how people interact and work together through daily life observations to find out the message of da'wah in the macopat tradition in the hamlet of morality, Karduluk village. There are four types of macopat traditions that are still alive and thriving in Moralas hamlet, Macopat mi'rad, Macopat nurbuwat, Macopat pandawa, Macopat agung-agung. the content of macopat contains da'wah in the macopat tradition in the hamlet of Moralas, namely regarding advice on the obligation to keep promises and intentions, the obligation to be grateful, seize the state and promote religion, the obligation to protect the youngest brother and provide annual expenditure (nyalenin), preach on goodness and also advises about retribution for his good and bad behavior like torment in hell. While the implementation of the macopat tradition preaches the importance of deliberation, strengthens friendly relations and creates warmth in togetherness, one cannot be separated from responsibility and how to give alms without having to be asked, respecting elders, praying at night is the right time and in it there are time that is istijabah and includes da'wah that involves direct behavior or is called da'wah bil hal because it is an example or role model. This research produces several important points about monotheism education in the story of Prophet Ibrahim according to Quraish Shihab in Tafsir al-Miṣhbāh. Tawhid education in the story of Prophet Ibrahim according to Quraish Shihab: a). Tawhid Education for Children b). Tawhid Education for the Prophet Ibrahim. The method of monotheism education in the story of Prophet Ibrahim: a) Scientific Method b) iwār Jadāli Method c) Exemplary Method d) Rational Method.